2008
DOI: 10.2350/07-01-0213.1
|View full text |Cite
|
Sign up to set email alerts
|

Less Invasive Autopsy: Benefits and Limitations of the Use of Magnetic Resonance Imaging in the Perinatal Postmortem

Abstract: The decline in the postmortem (PM) autopsy rate in the United Kingdom paralleled the change in public perception of this procedure after the organ retention crisis in 2000. The introduction of magnetic resonance imaging (MRI) in the fetal, perinatal, and pediatric autopsy led some investigators to propose that MRI could replace the conventional PM. We assessed the role of MRI in fetal autopsy as an addition or a potential replacement method to the conventional PM and to evaluate the benefits and limitations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 24 publications
0
42
1
1
Order By: Relevance
“…Of the 8 fetuses who had cardiac lesions, only 2 were detected by postmortem CMR imaging (25% sensitivity). Cohen et al 20 have reported 2 cases (no cardiac lesions) of postmortem CMR in sudden infant death; however, both the images were nondiagnostic.…”
Section: Previous Postmortem Cmr Imaging Studiesmentioning
confidence: 99%
“…Of the 8 fetuses who had cardiac lesions, only 2 were detected by postmortem CMR imaging (25% sensitivity). Cohen et al 20 have reported 2 cases (no cardiac lesions) of postmortem CMR in sudden infant death; however, both the images were nondiagnostic.…”
Section: Previous Postmortem Cmr Imaging Studiesmentioning
confidence: 99%
“…With a dedicated sequence, real-time MRI can be particularly useful for fetal cardiac assessment, which may lead to more effective antenatal intervention [41]. And lastly, MRI has been selectively used as an alternative for "less invasive" fetal autopsy [42].…”
Section: Miscellaneousmentioning
confidence: 99%
“…Although evaluation of the skeleton could be carried out by CT, this technique may allow assessment as part of a routine MR necropsy examination [12][13][14][15] without the need for a separate CT study. …”
Section: Potential Uses For Foetal Black Bone Mrimentioning
confidence: 99%